Advances in T Helper 17 Cell Biology: Pathogenic Role and Potential Therapy in Multiple Sclerosis. (7th December 2015) - Volpe, Elisabetta; Battistini, Luca; Borsellino, Giovanna
Abstract : The discovery of the T helper (Th) 17 lineage, involved in the protection against fungal and extracellular bacterial infections, has profoundly revolutionized our current understanding of T cell-mediated responses in autoimmune diseases, including multiple sclerosis (MS). Indeed, recent data demonstrate the pathogenic role of Th17 cells in autoimmune disorders. In particular, studies in MS and in its animal model (EAE, experimental autoimmune encephalomyelitis) have revealed a crucial role of Th17 cells in the pathogenesis of autoimmune demyelinating diseases in both mice and humans. Over the past years, several important aspects concerning Th17 cells have been elucidated, such as the factors which promote or inhibit their differentiation and the effector cytokines which mediate their responses. The identification of the features endowing Th17 cells with high pathogenicity in MS is of particular interest, and discoveries in Th17 cell biology and function could lead to the design of new strategies aimed at modulating the immune response in MS. Here, we will discuss recent advances in this field, with particular focus on the mechanisms conferring pathogenicity in MS and their potential modulation.